Teaching English in an engineering international branch campus: a collaborative autoethnography of our emotion labor - Sara Hillman (5981831) (2024)
While a number of studies have documented the significant role of emotions and the emotion labor produced in English language teaching, research exploring English instructors’ emotion labor in transnational higher education contexts such as international branch campuses (IBCs) and within Science, Technology, Engineering, and Math (STEM) programs is lacking. Arguably, these neoliberally-driven and educational neocolonialist endeavors can produce intense emotion labor for English instructors. This study employs a collaborative autoethnography (CAE) methodology to investigate what provoked emotion labor for expatriate instructors, who teach English courses to Qatari national students at an IBC in Qatar. Taking a poststructural approach to emotion labor as our theoretical framing, we collaboratively examined our emotion labor in audio-recorded weekly meetings and then engaged in further dialogues and writings about our emotion labor. We reflect on two themes that produced emotion labor as well as emotional capital for us: 1) navigating our purpose teaching English to engineering majors and 2) confronting our roles as English instructors within a context of educational neocolonialism. Our study adds to the knowledge base of English teachers’ emotion labor in transnational and STEM spaces, while also showcasing CAE as a transformative methodology to explore language teachers’ emotion labor. Other Information Published in: International Review of Applied Linguistics in Language Teaching License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1515/iral-2024-0078